Research on collaborative planning of distributed resources and energy storage in regional integrated energy system. Issue 1 (1st April 2022) - Ma, Zhoujun; Zhang, Yong
Abstract: Aiming at the problem of high operation cost caused by low energy utilization of users in the region, a collaborative planning method of distributed resources and energy storage of regional integrated energy system is proposed. We designed the operation framework of the regional integrated energy system, and described the operation state of the equipment and the energy coupling relationship. According to the relationship between cooling, heating and power supply, the objective function is established with the lowest total operating cost, the highest reliability and the highest system emission reduction rate, and the control constraints are established for the total load in the system. We have established a collaborative ownership model for distributed resources and energy storage, and distributed energy supply and energy storage equipment in the system. It enables each energy supply and energy storage device to adjust the operating mode according to its own needs. So as to realize the reasonable supply of energy and the economical and optimal operation of all users. Taking three typical users in a park as an example, the results show that the operating costs of the three users are reduced by 15532.92 yuan, 5906.63 yuan and 24495.62 yuan respectively. The planning method can not only ensure the stable operation of the energy system, but also reduce the operation cost of users.